2019
DOI: 10.2196/11665
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Recomposition of Norms and Representations in the Field of Psychiatry and Mental Health in the Age of Electronic Mental Health: Qualitative Study

Abstract: BackgroundFor the World Health Organization, electronic health (eHealth) is seen as an effective way to improve therapeutic practices and disease prevention in health. Digital tools lead to major changes in the field of mental medicine, but specific analyses are required to understand and accompany these changes.ObjectiveOur objective was to highlight the positions of the different stakeholders of the mental health care system on eHealth services and tools, as well as to establish professional and user group p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Engagement with digital technologies was influenced by emotional barriers such as feeling scrutinised [ 76 ], the perception of technologies as rigid and artificial [ 43 , 76 , 80 , 95 ], an unwillingness to spend additional time on technology after work [ 47 , 49 , 60 , 105 ], or feeling overwhelmed by the number of digital interventions available [ 41 , 55 , 58 , 101 , 104 ]. Improved access to care was broadly shown to facilitate implementation [ 41 , 50 , 56 ], with the most highly cited specific accessibility measures including flexibility and availability of digital technologies and resources when needed [ 39 , 40 , 46 , 47 , 49 , 54 , 56 , 60 , 75 , 78 , 85 , 88 , 97 , 98 , 100 , 103 ], and ease of integration into routine activities and places such as home or office [ 47 , 49 , 60 , 85 , 89 ]. Other facilitators included the ability to review materials and resources at a convenient time [ 49 ], reduced waiting times [ 37 , 54 , 74 , 94 ], reduced costs [ 61 , 84 ], enhanced choice of treatment delivery modalities [ 51 , 54 ], and providing an option for those who may not seek traditional face-to-face mental health care [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Engagement with digital technologies was influenced by emotional barriers such as feeling scrutinised [ 76 ], the perception of technologies as rigid and artificial [ 43 , 76 , 80 , 95 ], an unwillingness to spend additional time on technology after work [ 47 , 49 , 60 , 105 ], or feeling overwhelmed by the number of digital interventions available [ 41 , 55 , 58 , 101 , 104 ]. Improved access to care was broadly shown to facilitate implementation [ 41 , 50 , 56 ], with the most highly cited specific accessibility measures including flexibility and availability of digital technologies and resources when needed [ 39 , 40 , 46 , 47 , 49 , 54 , 56 , 60 , 75 , 78 , 85 , 88 , 97 , 98 , 100 , 103 ], and ease of integration into routine activities and places such as home or office [ 47 , 49 , 60 , 85 , 89 ]. Other facilitators included the ability to review materials and resources at a convenient time [ 49 ], reduced waiting times [ 37 , 54 , 74 , 94 ], reduced costs [ 61 , 84 ], enhanced choice of treatment delivery modalities [ 51 , 54 ], and providing an option for those who may not seek traditional face-to-face mental health care [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Absence of human interaction and non-verbal language, empathy, and impersonality has been cited as a barrier by both patients and providers [ 37 , 39 44 , 46 , 48 , 49 , 51 , 53 , 54 , 56 , 61 , 63 , 64 , 68 , 69 , 71 , 73 , 74 , 76 , 81 , 86 , 88 , 93 , 94 , 96 , 103 , 106 108 ]. As technology cannot fully replace human interactions for mental health care [ 40 , 49 , 90 , 97 ], some clinicians suggested that the most favourable place in therapy for digital interventions may be to complement and supplement face to face sessions [ 40 , 45 , 54 , 56 , 66 , 72 , 75 , 76 , 81 , 90 , 97 , 103 , 104 , 109 , 110 ], or to provide end of therapy support [ 67 , 100 ], rather than to substitute completely for traditional care.…”
Section: Resultsmentioning
confidence: 99%
“…Data from the free-association task suggest a relative openness or at least a lack of aversion to the mental health of participants. The subsequent focus group discussions also point in this direction, but nevertheless highlighted fears linked to “dehumanization” or the replacement of humans by technological tools [ 17 ]. The peripheral elements are linked to the structural and organizational dimensions of e-mental health (ie, “structure of care,” “organization”).…”
Section: Discussionmentioning
confidence: 99%
“…The first part of the study, based on data collected in focus groups, revealed a heterogeneous and unstable definition of e-mental health with regard to the different groups of actors concerned as well as within each group [ 17 ]. The second part of the study, presented here, is based on the free-association task method.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation